Development and Assessment of an In-Situ Gel for Ocular Drug Administration - Vishal Dubey, Akhilesh Pal, Rahul Pandey, Megha Tiwari, Archan Gupta (Journal of Neonatal Surgery, 2025)
Ophthalmic preparations are specialized dosage forms designed to be instilled onto the external surface of the eye (topical), administered inside the eye (intraocular) or adjacent to it (periocular, e.g., juxta scleral or subtenant), or used in conjunction with an ophthalmic device. The aim of the current study was to create an n-situ gel preparation i.e. sol to gel forming capability that would be able to maintain medication delivery to the eyes for extended time period without loss of drugs. the approach will be effective in treating infectious conditions such bacterial and viral infection, acute and sub-acute conjunctivitis and kerato conjunctivitis. Gellan gum and carbapol 934p were used as polymer in the creation of the gelling system. The various concentration of polymer used in formulation. All formulation were evaluated for clarity, pH, gelation duration, temperature gelling capacity in vitro study. Pre-formulation study of drug (acyclovir)Appearance -Order less Light white crystalline powder as reported in Literature.